THE ROLE OF ARGININE/CITRULLINE CYCLE DISORDERS IN THE PATHOGENESIS OF DOXORUBICIN-INDUCED LIVER INJURY ASSOCIATED WITH NONALCOHOLIC STEATOHEPATITIS IN RATS - Maslova, G.S.; Skrypnyk, R.I.; Gopko, O.F.; Skrypnyk, I.M. (World of Medicine and Biology, 2020)
The article presents the results of an experimental study aimed to investigate the features of arginine / citrulline cycle disorders associated with doxorubicin-induced liver injury in rats, concomitant with NASH. The study involved adult fertile outbred albino rats (n=30; male rats=15 (50%); female rats=15 (50%)) weighted 160-220 g. The rats were assigned into 3 groups: Group І (n=10) involved rats with NASH, administered with intraperitoneal 5 mg/kg doxorubicin for 3 days; Group ІІ (n=10) involved rats without NASH, administered with intraperitoneal doxorubicin similar to Group I regimen; Group ІІІ (n=10) – control group. It has been shown that administration of doxorubicin in rats with NASH leads to disorders of arginine/citrulline cycle, which are characterized by inhibition of arginase activity and activation of citrulline synthesis.